2017
DOI: 10.1016/j.esxm.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Linear Low-Intensity Extracorporeal Shockwave Therapy for Erectile Dysfunction—12-Month Follow-Up of a Randomized, Double-Blinded, Sham-Controlled Study

Abstract: IntroductionShort-term data on the effect of low-intensity extracorporeal shockwave therapy (Li-ESWT) on erectile dysfunction (ED) have been inconsistent. The suggested mechanisms of action of Li-ESWT on ED include stimulation of cell proliferation, tissue regeneration, and angiogenesis, which can be processes with a long generation time. Therefore, long-term data on the effect of Li-ESWT on ED are strongly warranted.AimTo assess the outcome at 6 and 12 months of linear Li-ESWT on ED from a previously publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 31 publications
(62 reference statements)
1
29
0
Order By: Relevance
“…2 ). However, the results from two randomised, sham-controlled studies, Fojecki et al and Olsen et al, did not reach the authors’ set threshold for significance at follow-ups of over 6 months [ 21 , 22 ]. The effects of LISWT were followed up for 24 months in one study, 12 months in four studies and 6 months in the remaining six studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). However, the results from two randomised, sham-controlled studies, Fojecki et al and Olsen et al, did not reach the authors’ set threshold for significance at follow-ups of over 6 months [ 21 , 22 ]. The effects of LISWT were followed up for 24 months in one study, 12 months in four studies and 6 months in the remaining six studies.…”
Section: Resultsmentioning
confidence: 99%
“…No studies identified an ongoing improvement at 12 months when compared to 6 months with two studies demonstrating plateauing of IIEF scores [ 15 , 18 ]. Three studies showed there was a gradual diminishing effect of effectiveness of LISWT beyond 6 months; however, scores remained at above baseline erectile function in all cases [ 13 , 16 , 21 ]. The largest of these studies demonstrating a gradual decline was conducted by Kitrey et al This prospective single-armed trial of 156 patients demonstrated an initial response rate of 63.5% at 1 month, decreasing to 42.9% at 12 months and declining to just 34% at 2-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a scientifically tested machine that had already been proven through 'sham control' to have certain positive effects on penile hemodynamics over a longer follow-up period. Recently, Fojecki et al [21] showed that exposure to two cycles of linear ESWT to treat ED was not superior to one cycle at the six-month and 12-month follow-up. Although they used a different machine with a linear probe and a five-week treatment session, the number of shockwaves and the energy flux density were the same.…”
Section: Discussionmentioning
confidence: 99%
“…A recent RCT performed on 126 men in a Danish hospital compared men who received five versus ten sessions at 6 and 12 months; treatment was approximately 38% effective in both groups, suggesting that additional sessions may not improve outcome. 150,151 In a 2 year follow-up of an open-label trial of 156 men, 63% improved at 4 weeks with 53% effectiveness sustained at 2 years. 152 Not surprisingly, men with severe ED had earlier failure.…”
Section: Low-intensity Extracorporeal Shockwave Therapymentioning
confidence: 99%